Meningkatkan Hasil Belajar Passing Bawah Bola voli Melalui Model Pembelajaran Resiprokal - Ahmad, Khairul; Porja Daryanto, Zusyah (Universitas PGRI Pontianak, 2023)
The title of this study is an attempt to improve the learning of volleyball underhand passing with a reciprocal teaching style in class VIII C students of SMP Negeri 3 Jawai, Sambas Regency. The problem in this study is how to improve the learning of passing under volleyball with a reciprocal teaching style in class VIII C students of SMP Negeri 3 Jawai, Sambas Regency? In particular, this study aims to describe the planning, implementation, observation, reflection and improvement of volleyball underhand passing learning with a reciprocal teaching style in class VIII C students of SMP Negeri 3 Jawai, Sambas Regency. The results showed that using a reciprocal teaching style could increase the learning outcomes of passing under volleyball. From the test results in cycle II it showed that the learning outcomes of passing under volleyball carried out by students increased from 26% in the initial conditions to 44.11% at the end cycle I and increased to 79.41% at the end of cycle II. The target achievement indicator in cycle II is 75%. From the student learning outcomes shown, the percentage of completeness of student learning outcomes is 79.41%, meaning that the achievement target in cycle II has been achieved.. Hasil penelitian menunjukan bahwa dengan menggunakan gaya mengajar resiprokal dapat meningkat hasil belajar passing bawah bola voli, Dari hasil tes pada siklus II menunjukkan bahwa hasil belajar Passing bawah bola voli yang dilakukan oleh siswa meningkat dari 26% pada kondisi awal menjadi 44,11% pada akhir siklus I dan meningkat menjadi 79,41% pada akhir siklus II. Indikator target capaian pada siklus II adalah 75%. Dari hasil belajar siswa yang ditunjukkan, prosentase ketuntasan hasil belajar siswa adalah 79,41%, artinya target capaian pada siklus II sudah tercapai.